The coming and going of a marl lake: multi-indicator palaeolimnology reveals abrupt ecological change and alternative views of reference conditions - Wiik, Emma; Bennion, Helen; Sayer, Carl D.; Davidson, Thomas A.; Clarke, Stewart J.; McGowan, Suzanne; Prentice, Stephen; Simpson, Gavin; Stone, Laura (Frontiers in Ecology and Evolution, 2015)
Eutrophication is the most pressing threat to highly calcareous (marl) lakes in Europe. Despite their unique chemistry and biology, comprehensive studies into their unimpacted conditions and eutrophication responses are underrepresented in conservation literature. A multi-indicator palaeolimnological study spanning ca 1260 to 2009 was undertaken at Cunswick Tarn (UK), a small, presently eutrophic marl lake, in order to capture centennial timescales of impact. Specific aims were to 1) establish temporal patterns of change (gradual/abrupt) across biological groups, thereby testing theories of resistance of marl lake benthic communities to enrichment, and 2) compare the core record of reference condition with prevailing descriptions of high ecological status. Analyses of sediment calcium (Ca), phosphorus (P), pigments, diatoms, testate amoebae, cladocerans, and macrofossils, revealed three abrupt changes in ecosystem structure. The first (1900s), with biomass increases in charophytes and other benthic nutrient-poor indicators, supported ideas of resistance to eutrophication in Chara lakes. The second transition (1930s), from charophyte to angiosperm dominance, occurred alongside reductions in macrophyte cover, increases in eutrophic indicators, and a breakdown in marling, in support of ideas of threshold responses to enrichment. Core P increased consistently into the 1990s when rapid transitions into pelagic shallow lake ecology occurred and Cunswick Tarn became biologically unidentifiable as a marl lake. The moderate total P at which these changes occurred suggests high sensitivity of marl lakes to eutrophication. Further, the early record challenges ideas of correlation between ecological condition, charophyte biomass and sediment Ca. Instead, low benthic production, macrophyte cover, and Ca sedimentation, was inferred. Management measures must focus on reducing external nutrient and sediment loads at early stages of impact in order to preserve marl lakes.